Spiritual Ends Religion and the Heart of Dying in Japan - Benedict, Timothy O. (University of California Press, 2023)
What role does religion play at the end of life in Japan? Spiritual Ends draws on ethnographic fieldwork and interviews to provide an intimate portrayal of how spiritual care is provided to the dying in Japan. Timothy O. Benedict shows how hospice caregivers in Japan are appropriating and reinterpreting global ideas about spirituality and the practice of spiritual care. Benedict relates these findings to a longer story of how Japanese religious groups have pursued vocational roles in medical institutions as a means to demonstrate a so-called "healthy" role in society. Focusing on how care for the kokoro (heart or mind) is key to the practice of spiritual care, this book enriches conventional understandings of religious identity in Japan while offering a valuable East Asian perspective to global conversations on the ways religion, spirituality, and medicine intersect at death. "Timothy Benedict has produced a work brimming with wisdom drawn from his work as a chaplain as well as a broad understanding of the place of religion in the lives of contemporary Japanese people." - HELEN HARDACRE, Reischauer Institute Professor of Japanese Religions and Society, Harvard University "Benedict offers a highly original perspective and new insightful material, providing a critical approach to the debate about spiritual care and spirituality." - ERICA BAFFELLI, Professor of Japanese Studies, University of Manchester "Spiritual Ends reveals an unassuming approach to spiritual care that privileges human connections at life's end." - JACQUELINE STONE, author of Right Thoughts at the Last Moment: Buddhism and Deathbed Practices in Early Medieval Japan "A discerning study of pain and comfort at the end of life, and a story of the invention of spirituality in Japan, which traffics between medical, psychological, and religious thought." - AMY B. BOROVOY, Professor of East Asian Studies, Princeton University